Effects of project-based learning on environmental literacy of pre-service teachers at an Institute of Teacher Education in Malaysia - Shaik Ismail, Nazifah (2013)
This study was undertaken in response to the need for empirical research concerning the effectiveness of instructional approaches implemented in environmental education programmes. The intent of this quasi-experimental research with pre-test, post-test and delayed post-test non-equivalent control group design is to study the impact of the project based learning instructional approach on the environmental literacy of pre-service teachers. The study involves 131 pre-service teachers (experimental group = 67, control group = 64) from the Institute of Teacher Education. Project-based learning instructional method was applied to the experimental group whereas teaching and learning strategies specified by the curriculum standards was applied to the control group. Environmental literacy survey was used to gather quantitative data whereas student reflective journals were analyzed for the qualitative insights. The validation procedure of the environmental literacy survey involves translation validity, content validity, pilot test, reliability test and construct validity. Content validation indexes for the environmental literacy survey are above 0.90 for all the components whereas the reliability indexes are above 0.75. The construct validity requirements were also satisfied as the CMIN/DF is 2.26; GFI is .92; CFI is .93; TLI is .91; and the RMSEA is .07. The kappa values obtained for qualitative data was above 0.86 indicating that the qualitative analysis was valid. The results gathered based on combined scores of each component of environmental literacy indicated that project based learning instructional method was more effective in enhancing the affective (t = 3.11, p < 0.05) and cognitive (t = 3.44, p < 0.05) components of environmental literacy in comparison to the combination of the multiple student centred strategies specified by the curriculum standards. Based on the effect size derived from paired sample t-test, the eta squared value observed for the affective component of the experimental group (2 = 0.47) is larger than the control group ( 2 = 0.37). Similar results was observed for the cognitive component, where the effect size of the experimental group is 0.77 and the effect size of the control group is 0.60. In the case of behaviour component of environmental literacy, there is no significant difference in the combined mean scores of the experimental and the control group. However, when analysed based on the subscale level, the project-based learning instructional method proved to be significantly more effective in increasing the “Eco-management” subscale of the behaviour component of environmental literacy (t = 3.28, p < 0.05). Qualitative analysis showed the improvement in values and beliefs towards the environment, sense of obligation towards the environment, individual actions towards improving the environment and environmental knowledge were attributed to discussion and knowledge sharing activities which were triggered by the leading questions embedded in the project. Through these activities, the students gained insightful knowledge that induced the changes in how they feel about the environment and the values that they hold. The knowledge that they have gained had also induced the students to change their lifestyle towards preserving the environment. This study indicated that project-based learning instructional method in environmental education is more effective than a combination of different instructional strategies in improving the environmental literacy of pre-service teachers in Malaysia. The retention analysis on the delayed post-test mean scores showed that environmental literacy did not persist especially for the behaviour component of environmental literacy. However, the mean scores were still significantly higher than the pre-test mean scores. Perhaps, the cultivation of environmental literacy might be more efficient if the programme involves long-term initiatives and many enhancements opportunities. Further investigation needs to be conducted to establish the reasons some subscales increased more or persist more than the others.